Enabling collaborative synthesis in multi-partner programmes - and Cochrane, Logan; Cundill, Georgina (Development in Practice, 2018)
Multi-partner consortia have emerged as an important modality for knowledge generation to address complex sustainability challenges. Establishing effective multi-partner consortia involves significant investment. This article shares lessons from the Collaborative Adaptation Research Initiative in Africa and Asia (CARIAA), which aims to support policy and practice for climate change adaptation through a consortium model. Key lessons include the need to facilitate collaborative spaces to build trust and identify common interests, while accepting that this is not a guarantee of success; the importance of programmatic leadership to achieve synthesis; and the value of strategic planning in supporting motivation and alignment between partners.